2014
DOI: 10.1111/gfs.12151
|View full text |Cite
|
Sign up to set email alerts
|

Yearly variation in maize silage fermentation and nutritive quality

Abstract: A significant effect of year on maize nutritive value has been reported in many studies; however, the direct effect of year on both nutritive values and fermentation traits of maize silage has not been directly investigated. During a 7‐year period (2006–2012), we investigated the following variables of 597 maize silages commercially produced in bunker silos on farms in the Czech Republic: dry‐matter content (DM), crude protein (CP), starch, amylase‐treated neutral detergent fibre (aNDF), acid detergent fibre (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
1
5
0
1
Order By: Relevance
“…The decisive factor affecting the silage nutritive value is the harvesting stage, and the fermentation process was reported to only have a slight impact on the nutritive value of maize silage [ 32 ]; this conclusion was verified partly in this study. The effects of different additives on the protein contents of silages were not significant; the fermentation time affected the dry matter significantly, the dry matter decreased with the fermentation time increased.…”
Section: Discussionsupporting
confidence: 66%
“…The decisive factor affecting the silage nutritive value is the harvesting stage, and the fermentation process was reported to only have a slight impact on the nutritive value of maize silage [ 32 ]; this conclusion was verified partly in this study. The effects of different additives on the protein contents of silages were not significant; the fermentation time affected the dry matter significantly, the dry matter decreased with the fermentation time increased.…”
Section: Discussionsupporting
confidence: 66%
“…Corn ( Zea mays L.) is considered to have consistent nutritional qualities and a high energy value, and it is relatively easy to grow and conserve (Loucka et al . ). It is the most popular cereal crop conserved as silage in many parts of the world (McDonald et al .…”
Section: Introductionmentioning
confidence: 97%
“…Wen et al (2011) found high quality silage was obtained by ensiling alfalfa with Italian ryegrass, and the optimal ratio of alfalfa to Italian ryegrass was 7:3. Corn (Zea mays L.) is considered to have consistent nutritional qualities and a high energy value, and it is relatively easy to grow and conserve (Loucka et al 2014). It is the most popular cereal crop conserved as silage in many parts of the world (McDonald et al 1991) due to its relatively high DM content, low buffering capacity and high WSC for fermentation to lactic acid, which is responsible for the reduction of pH to the required level (Meeske and Basson 1998).…”
Section: Introductionmentioning
confidence: 99%
“…According to Goeser et al (2015), the DM losses in the fodder occur in the fermentation processes and even at silo opening; therefore, as the pH and DM content are strongly related, fodder with low DM contents (between 300 and 350 g kg -1 ) should be avoided for ensilage. In addition, plant silage with optimal DM content contributes to reduced concentrations of mycotoxins (LOUČKA et al, 2014;SCHMIDT et al, 2015).…”
Section: Resultsmentioning
confidence: 99%